A new method for quantification of frontal retrusion and complex skull shape in metopic craniosynostosis: a pilot study of a new outcome measure for endoscopic strip craniectomy - SAÇAK, BÜLENT; ERDOĞAN, ONUR; BAYRİ, YAŞAR; DAĞÇINAR, ADNAN; SAKAR, MUSTAFA; SÖNMEZ, ÖZCAN (My University, 2022)
OBJECTIVE The objective of this study was to propose a new skull outline–based method to objectively quantify complex 3D skull shapes and frontal and supraorbital retrusion in metopic craniosynostosis using 3D photogrammetry. METHODS A standard section from 3D photogrammetry, which represents the trigonocephalic shape, was used in this study. From the midpoint of the area of this section, half diagonals were calculated to the skull outline at 5° increments in the anterior half of the head. These half diagonals were used to create a sinusoidal curve, and the area under the sinusoidal curve (AUC) was used to represent the mathematical expression of the trigonocephalic head shape. The AUC from 0° to 180° (90° from the midline to each side) was calculated and is referred to as AUC0→180. The AUC from 60° to 120° (30° from the midline to each side) was also calculated and is referred to as AUC60→120. A total of 24 patients who underwent endoscopic strip craniectomy and 13 age- and sex-matched controls were included in the study. The AUC values obtained in patients at different time points and controls were analyzed. RESULTS The mean preoperative AUC60→120 and AUC0→180 in the patients were significantly lower than those in control individuals. The increase in both AUC60→120 and AUC0→180 values is statistically significant at the discontinuation of helmet therapy and at final follow-up. Receiver operating characteristic curve analysis indicated that AUC60→120 is a more accurate classifier than AUC0→180. CONCLUSIONS The proposed method objectively quantifies complex head shape and frontal retrusion in patients with metopic craniosynostosis and provides a quantitative measure for follow-up after surgical treatment. It avoids ionizing radiation exposure
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Nöroloji; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; Neurology; Surgery Medicine Sciences; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); PEDİATRİ; CERRAHİ; CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); PEDIATRICS; SURGERY; Pediatri; Nöroloji (klinik); Cerrahi; Pediatri, Perinatoloji ve Çocuk Sağlığı; Yaşam Bilimleri; Pediatrics; Neurology (clinical); Surgery; Pediatrics, Perinatology and Child Health; Life Sciences; metopic craniosynostosis; endoscopic strip craniectomy; quantification; frontal retrusion; supraorbital retrusion; 3D photogrammetry; craniofacial; QUANTITATIVE ASSESSMENT; COMPUTED-TOMOGRAPHY; SYNOSTOSIS; CT; SEVERITY; VOLUME; HEAD; metopic craniosynostosis; endoscopic strip craniectomy; quantification; frontal retrusion; supraorbital retrusion; 3D photogrammetry; craniofacial